What Does a Job Candidate's Age Signal to Employers? - Hannah Van Borm; Ian Burn; Stijn Baert (Global Labor Organization (GLO), 2019)
Research has shown that hiring discrimination is a barrier for older job candidates in many OECD countries. However, little research has delved into why older job candidates are discriminated against. Therefore, we have conducted an online scenario experiment involving recruiters to empirically investigate 15 potential stigma related to older age drawn from a systematic review of the literature. We found that older age particularly signals to recruiters that the applicant has lower technological skill, flexibility, and trainability levels. Together, these perceptions explain about 41% of the effect of age on the probability of being invited to a job interview. In addition, we found that the negative association between age and invitation probability is smaller when recruiters work for firms with a higher percentage of older employees.
Keywords: J71; J14; J24; J23; 330; hiring; statistical discrimination; age; stereotypes